العناصرالدالليةفي غالف أغذيةاملجمدةالحالل:دراسةوصفيةتحليلية - Zalika Adam; Lubna Abd Rahman; Jamal Abdul Nassir Shaari; Nurul Aisyah binti Hasan Basri; Youcef Nasser (Universitas Muhammadiyah Sumatera Barat, Indonesia, 2024)
Most of Malaysians choose frozen food in their lives because of its quick preparation and availability. The indicative elements are usually displayed on the packaging of frozen food to know its components, method of preparation, production and expiry date. This study aims to discover the semantic elements present in the packaging of frozen food, to know the semantic elements depicted and their role in this packaging, and to know the effects of the semantic elements on consumers. The study followed the descriptive analytical approach, which is the description of halal frozen food and the analysis of the interview conducted with the participants. This study consists of three participants to know the experiences and their attention on the semantic elements in the cover. The data was analyzed by extracting important insights using Atlas.ti. The results of the study indicated there of; The semantic elements in the packaging have an impact on consumers. The study ended with recommendations and suggestions.